The leadership challenge : how to make extraordinary things happen in organizations - Kouzes, James M. , 1945-; Posner, Barry Z. (San Francisco, California : The Leadership Challenge, 2012)
The 25th anniversary edition of the business classic, completely revised and updated. The Leadership Challenge, based on Kouzes and Posner's extensive research, this all-new edition casts their enduring work in context for today's world, proving how leadership is a relationship that must be nurtured and can be learned. Features over 100 all-new case studies and examples, which show The FivePractices of Exemplary Leadership in action around the world. Focuses on toughest organizational challenges leaders face today. Addresses changes in how people work and what people want from their work. It is an indispensable resource for leaders at all levels.
1. When leaders are at their best -- 2. Clarify values -- 3. Set the example -- 4. Envision the future -- 5. Enlist others -- 6. Search for opportunities -- 7. Experiment and take risks -- 8. Foster collaboration -- 9. Strengthen others -- 10. Recognize contributions -- 11. Celebrate the values and victories -- 12. Leadership Is everyone's business
Includes bibliographical references and index
Keywords: Executive ability; Leadership; Management